2019
DOI: 10.1029/2019gl085116
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Response of Sea Ice to Warming in the Canadian Arctic Archipelago

Abstract: Ice arches in the Canadian Arctic Archipelago (CAA) block the inflow of Arctic Ocean ice for the majority of the year. A 22 year record (1997–2018) of Arctic Ocean‐CAA ice exchange was used to investigate the effect of warming on CAA sea ice dynamics. Larger ice area flux values were associated with longer flow duration and faster ice speed facilitated by increased open water leeway from the CAA's transition to a younger and thinner ice regime, which together have contributed to a significant ice area flux inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…The impact of the 2017 reversal on the distribution of MYI highlights the precarious nature of the remaining MYI in the central Arctic which is becoming increasingly mobile and can either be: (i) advected into the Beaufort Sea where a majority, if not all, will now melt during the subsequent summer (Babb et al., 2016, 2019; Kwok & Cunningham, 2010; Maslanik et al., 2011; Stroeve et al., 2011), (ii) exported through Fram Strait into the North Atlantic where it melts (Hansen et al., 2013; Kwok, 2009), iii) exported through the increasingly mobile Nares Strait into Baffin Bay (Kwok et al., 2010; Moore & McNeil, 2018; Ryan & Münchow, 2017) where it may be transported great distances (Barber et al., 2018) but does eventually melt out in the Labrador Sea or Baffin Bay, or iv) exported into the increasingly mobile CAA where it may persist for several years as it gradually migrates through the region (Howell & Brady, 2019; Howell et al., 2013) toward the Northwest Passage (Haas & Howell, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of the 2017 reversal on the distribution of MYI highlights the precarious nature of the remaining MYI in the central Arctic which is becoming increasingly mobile and can either be: (i) advected into the Beaufort Sea where a majority, if not all, will now melt during the subsequent summer (Babb et al., 2016, 2019; Kwok & Cunningham, 2010; Maslanik et al., 2011; Stroeve et al., 2011), (ii) exported through Fram Strait into the North Atlantic where it melts (Hansen et al., 2013; Kwok, 2009), iii) exported through the increasingly mobile Nares Strait into Baffin Bay (Kwok et al., 2010; Moore & McNeil, 2018; Ryan & Münchow, 2017) where it may be transported great distances (Barber et al., 2018) but does eventually melt out in the Labrador Sea or Baffin Bay, or iv) exported into the increasingly mobile CAA where it may persist for several years as it gradually migrates through the region (Howell & Brady, 2019; Howell et al., 2013) toward the Northwest Passage (Haas & Howell, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the 2017 reversal on the distribution of MYI highlights the precarious nature of the remaining MYI in the central Arctic which is becoming increasingly mobile and can either be: (i) advected into the Beaufort Sea where a majority, if not all, will now melt during the subsequent summer (Babb et al, 2016(Babb et al, , 2019Kwok & Cunningham, 2010;Maslanik et al, 2011;Stroeve et al, 2011), (ii) exported through Fram Strait into the North Atlantic where it melts (Hansen et al, 2013;Kwok, 2009), iii) exported through the increasingly mobile Nares Strait into Baffin Bay Moore & McNeil, 2018;Ryan & Münchow, 2017) where it may be transported great distances (Barber et al, 2018) but does eventually melt out in the Labrador Sea or Baffin Bay, or iv) exported into the increasingly mobile CAA where it may persist for several years as it gradually migrates through the region (Howell & Brady, 2019;Howell et al, 2013) The loss of MYI in the Arctic Ocean remains one of the key climate-induced changes of the northern polar environment, and due to its location within the Beaufort Gyre the Beaufort Sea is a critical area for MYI. Whereas once the Beaufort acted as the "safest" haven for MYI exiting the Central Arctic, providing a route for floes to circulate within the ocean for many years, several studies have shown that it is now increasingly unlikely this ice can even last one summer transiting the Beaufort Sea.…”
Section: The Impact Of the Reversal On The Distribution Of Myimentioning
confidence: 99%
“…Mahmud et al 2016;Marshall et al 2019). Furthermore, the effect of warming on sea ice dynamics in this region can be counterintuitive as warming could result in increased ice import from the Arctic Ocean into the CAA (Melling, 2002;Howell and Brady, 2019;Moore et al, 2021). Therefore, monitoring Arctic snow and ice cover is critical to improve our understanding of this complex and variable region in the context of climate variability and change.…”
Section: Introductionmentioning
confidence: 99%
“…Active microwave algorithms using synthetic aperture radar (SAR) provide high resolution (20 to 100 m) retrieval of snow and ice parameters (e.g. Surdu et al 2016;Zhu et al 2018;Howell and Brady, 2019). SAR estimates of snow and ice cover provide the highest spatial resolution compared to other products, however the moderate temporal resolution, narrow swath width, and limited image availability across the Arctic limits the application of SAR to smaller geographic regions (Brown et al 2014;Howell et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, modelling the CAA still remains challenging because complex sea ice dynamic and thermodynamic processes are often not accurately resolved in its narrow channels and inlets. In addition, the response of the CAA to climatic change is perhaps counter-intuitive as longer melt seasons are resulting in increased MYI import from the Arctic Ocean during the summer months (Howell and Brady, 2019). Since f pk is linked to summer sea ice melt processes (e.g.…”
Section: Introductionmentioning
confidence: 99%